"Model-based" design of thermal management system of a fuel cell "air-independent" propulsion system for underwater shipboard. (13th November 2020) - Han, Jaeyoung; Han, Jaesu; Ji, Hyunjin; Yu, Sangseok
Abstract: The thermal management of the fuel cell stack is critical for high-performance long-term operation. A fuel cell system of underwater vessel has a liquid-to-liquid cooling circuits which is composed of two liquid cooling pumps, two three-way valves, and a shell and tube heat exchanger. The liquid-to-liquid cooling technique makes it easier to reject the reaction heat into the surrounding but it is required refined cooling structure and control algorithm. In this study, a model-based design is applied to evaluate the control algorithm. A fuel cell system simulation model is developed and polarization curves and transient response are validated. A proportional integral controller and control strategy is developed and a nominal state feedback controller is also developed. Those control algorithms are evaluated via the dynamic response under step increases of load, and the control performance of the nominal state feedback controller is compared with the conventional controller (PI). The results show that the presented the nominal state feedback control of performs better than the PI control method with less wear and less control effort on the two circuit cooling modules. The proposed the nominal state feedback control can increase the system energy by 23.9%. Highlights: A liqud-to-liquid cooling technology for air independent fuel cell system was presented. Thermal management system was composed of a 1st and 2nd cooling system. Experiments were conducted to verify the designed system model. Two controllers were developed to evaluate the control performance. Required cooling performance was achieved by liquid-to-liquid cooling.